SISTEM PENGELOLAAN KURIKULUM, ABSENSI DOSEN DAN KULIAH PENGGANTI PADA FAKULTAS TEKNOLOGI INFORMASI UNIVERSITAS TARUMANAGARA - Yunita Yunita; Lely Hiryanto (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
The developed application consist of three parts, curriculum operational manager,lecturer’s absence manager and scheduling of substitute course. The curriculum operational manager is used as a tool to create a computerized curriculum operational’s report. Meanwhile, the lecturer’s absence manager is created to count the absence of the lecturer and generating a lecturer absence recapitulation’s document. The Constraint Based Reasoning Algorithm will be combined with Great Deluge Algorithm to get a suitable room and time slot for the needed substitute course. The application’s testing result’s shows that the system has been able to generate curriculum operatinal’s report and lecturer’s absence report according to the prescribed format. Testing to the substitute course scheduling is conducted on Faculty of  Information Technology Tarumanagara University’s 2012/2013 odd semester’s schedule and the result shows that there was no violation of the provisions of existing substitute course schedule’s rule.